Experimental Analysis on Compression Characteristics of Improved Phyllite Filler - ZHANG Yang (Renmin Zhujiang)
Soil compression is an important characteristic that affect the construction and operation of improved soft rock filling in mountainous ports.Through adding 5% cement to improve the weakly weathered phyllite filler,setting 4 kinds of rolling loads and 5 cycles of loading and unloading,and using an improved high-pressure lever consolidation instrument,this paper measures the soil strain,compaction and porosity ratio under different stress states,and specifies the change law of compression modulus and resilience modulus during loading and unloading process.The test results shows that:The deformation of the modified phyllite filler mainly occurs in the first loading process,and it increases significantly with the increase of the rolling load.The porosity ratio curve shows a concave shape with the increased cycles of loading and unloading.When the rolling load is 100 kPa,the curve of porosity ratio is nonlinear with the increased cycles of loading and unloading;when the rolling load is 200 kPa,the compression of the soil changes from medium to low with the increase of compaction cycles.At this time,the modulus of resilience takes a minimum value.It is suggested that the 200 kPa roller compaction stress should be used as the first static compaction during the construction of improved soft rock filling in mountainous ports,which should be increased appropriately in the subsequent construction.